2021
DOI: 10.3390/agronomy11112176
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Forage Nutritive Quality of Alfalfa and Red Clover through Plant Breeding

Abstract: Alfalfa and red clover are important perennial legumes for the production of high-quality fodder. The improvement of the forage quality of legumes is one of the strategic goals of breeding programs. Variation in quality traits (protein content (CP), neutral detergent fiber content (NDF), and acid detergent fiber content (ADF)) and relative feed value (RFV) among seven cultivars and 39 elite breeding populations of alfalfa and red clover was evaluated in the study. Significant differences were determined among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Fibre is often regarded as the negative index of nutritive quality 47 , 48 . It is negatively related to digestibility of feed, as lower the concentration of fibre in feed it become easier to digest which results in good energy value 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibre is often regarded as the negative index of nutritive quality 47 , 48 . It is negatively related to digestibility of feed, as lower the concentration of fibre in feed it become easier to digest which results in good energy value 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas neutral detergent fibre (NDF), acid detergent fibre (ADF), acid lignin fibre (ADL) were done by adopting the methodology prescribed by Van Soest et al . 48 . Cellulose and hemicellulose contents were calculated by the formulae Cellulose = ADF-ADL, Hemicellulose = NDF-ADF 48 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the extensive research of Medicago species triterpene saponins and phytoestrogens [ 12 , 13 , 14 ], alfalfa contains potentially valuable phenolics with an excellent ability to capture oxidative free radicals [ 12 , 15 ]. Several classes of alfalfa phenolics were reported in the literature, and among them, phenolic acids and flavonoids are widely present [ 9 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa, a kind of green fodder in traditional-style pig feeding systems in China, contains mainly insoluble dietary fiber, including cellulose, xylans, and lignin (5,6). However, other studies have reported that diets with a high fiber content may negatively affect feed intake and nutrient digestibility in growing pigs.…”
Section: Introductionmentioning
confidence: 99%